Pengembangan Media Pembelajaran Interaktif Articulate Storyline Pada Materi Pesawat Sederhana Kelas VIII SMP - Ikrimah Sari; Maya Istyadji; Rizky Febriyani Putri (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
Research on improving easy-to-understand storyline media on basic subject matter intends to illustrate the legitimacy of informative media. The 4D development model (define, design, develop, deploy) uses R&D methods in research. The percentage method of the expert validation sheet is used for the data collection method. The consequence of this review shows that intelligent learning media with expressive storylines gets a legitimacy score of 87%. Based on these findings, it can be concluded that the simple field material of Articulate Storyline is said to be very useful for learning natural sciences in junior high schools.